Monetary policy, bank capital and credit supply: a role for discouraged and informally rejected firms - Alexander Popov (European Central Bank (ECB), 2013)
This paper conducts the first empirical study of the bank balance sheet channel using data on discouraged and informally rejected firms in addition to information on the formal loan granting process. I take advantage of a unique survey data on the credit experience of firms in 8 economies that use the euro or are pegged to it over 2004-2007, and analyze the effect of monetary policy and the business cycle on bank lending and risk-taking. Identification rests on exploiting 1) the exogeneity of monetary policy to local business cycles, and 2) firm-level and bank-level data to separate the supply of credit from changes in the level and composition of credit demand. Consistent with previous studies, I find that lax monetary conditions increase bank credit in general and bank credit to ex-ante risky firms in particular, especially for banks with lower capital ratios. Importantly, I find that the results are considerably stronger when data on informal credit constraints are incorporated.
Keywords: E32; E51; E52; F34; G21; 330; bank capital; bank lending channel; business cycle; cross-border lending; monetary policy